Indian agritourism industry- an instrument of economic development - Bala Krishnan, C; Radhikaa Shree, M; Asrafi, S (International Journal of Engineering and Technology, 2018)
Tourism is also well recognized as an engine of growth in the various economics in the world. It has emerged as one of the largest global economic activities. Several countries have transformed their economics by developing their tourism potential. Tourism has great capacity to generate large scale employment and additional income source to the skilled and unskilled.As per the estimate of world Travel and Tourism council (W.T.T.C) tourism generated more than worth 5 trillion of output equivalent to about 8% of total world G.N.P India’s share of world tourist advent has been merely 4% W.T.T.O in its tourism vision 2020 has projected that there would be about 1.6 billion International tourists in all countries of the world by the year 2020. As per the same assessment India is expected to fuel 4.5 times growth international tourist destination thus playing a major role in the economy of the states.